Intra‐Target Microdosing – A Novel Drug Development Approach: Proof of Concept, Safety, and Feasibility Study in Humans. Issue 5 (8th July 2017) - Burt, T; MacLeod, D; Lee, K; Santoro, A; DeMasi, DK; Hawk, T; Feinglos, M; Rowland, M; Noveck, RJ
Abstract: Intra‐Target Microdosing (ITM) is a novel drug development approach aimed at increasing the efficiency of first‐in‐human (FIH) testing of new molecular entities (NMEs). ITM combines intra‐target drug delivery and "microdosing, " the subpharmacological systemic exposure. We hypothesized that when the target tissue is small (about 1/100th of total body mass), ITM can lead to target therapeutic‐level exposure with minimal (microdose) systemic exposure. Each of five healthy male volunteers received insulin microdose into the radial artery or full therapeutic dose intravenously in separate visits. Insulin and glucose levels were similar between systemic administration and ITM administration in the ipsilateral hand, and glucose levels demonstrated a reduction in the ipsilateral hand but not in the contralateral hand. Positron emission tomography (PET) imaging of 18 F‐fluorodeoxyglucose (FDG) uptake demonstrated differences between the ipsilateral and contralateral arms. The procedures were safe and well‐tolerated. Results are consistent with ITM proof‐of‐concept (POC) and demonstrate the ethical, regulatory, and logistical feasibility of the approach.